1978
DOI: 10.1017/s0043174500049808
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Germination, Emergence, and Seed Production of ThreeIpomoeaTaxa

Abstract: The influence of seed age, planting depth, and temperature on the germination and emergence of ivyleaf morningglory [Ipomoea hederacea(L.) Jacq. var.hederacea], white morningglory(Ipomoea lacunosaL.), and entireleaf morningglory(Ipomoea hederaceavar.integriusculaGray) was studied by using pure seed of each taxa that were collected in 1972, 1973, and 1974. Germination of acid-scarified white and entireleaf morningglory seed ranged from 64 to 98% at continuous 20, 25, 30, 35, and 40 C and at an alternating 20/30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 7 publications
3
40
1
1
Order By: Relevance
“…3). Studies by Stoller and Wax (1974) and Gomes et al (1978) also showed that seeds of /. bederacea germinate In summer.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…3). Studies by Stoller and Wax (1974) and Gomes et al (1978) also showed that seeds of /. bederacea germinate In summer.…”
Section: Discussionmentioning
confidence: 92%
“…hederacea seeds germinated over a wide range of temperatures ( 16°-32°C) and osmotic potentials (0-10 bars (0-1.0 MPa]), whereas nonscarified intact seeds germinated to <20% in all temperatures tested (Crowley and Buchanan 1980). Gomes et al (1978) reported that <20% of the scarified seeds of this species germinated at 40°C, whereas none of the nonscarified seeds germinated at this temperature.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although pitted morningglory has a hard seed coat (Gomes et al 1978), the nondormant portion of the seed population emerged soon after planting both years, especially in 2003 when 80% of the total emergence occurred by 7 DAE. Because a large percentage of the total number of seedlings emerged soon after planting with minimal emergence throughout the remainder of the study, it was difficult to fully evaluate whether soybean canopy formation influences pitted morningglory emergence.…”
Section: Weed Emergencementioning
confidence: 99%
“…Germination was determined by placing 50 seeds in a 10-cm-diameter petri dish with a filter paper to maintain moisture and 10 ml deionized-distilled water. Seeds were placed in a germination chamber at 28 C, and germination was determined after 10 d (Creel et al 1968;Gomes et al 1978) considering a seed germinated when the radicle was at least 5 mm long.…”
Section: Methodsmentioning
confidence: 99%